2011
DOI: 10.1186/1752-1947-5-340
|View full text |Cite
|
Sign up to set email alerts
|

Adult granulosa cell tumor associated with endometrial carcinoma: a case report

Abstract: IntroductionIf strict criteria for the diagnosis of carcinoma are used and all patients with granulosa cell tumors are considered, the best estimate of the incidence of associated endometrial carcinomas is under 5%. In patients with granulosa cell tumors, estrogen-dependent endometrial cancers are rarely found, and most of these endometrial cancers are well-differentiated endometrioid adenocarcinomas that carry a good prognosis when detected early.Case presentationWe report the case of a 65-year-old post-menop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 7 publications
1
27
0
1
Order By: Relevance
“…This is of utmost importance, as it may lead to endometrial abnormalities with an incidence of 30-85% endometrial hyperplasia and 3-20% endometrial carcinoma. (9,23,24) In our study hyperplasia was documented in 26% of all group with no endometrial carcinoma found, which matches the international results.…”
Section: Discussionsupporting
confidence: 90%
“…This is of utmost importance, as it may lead to endometrial abnormalities with an incidence of 30-85% endometrial hyperplasia and 3-20% endometrial carcinoma. (9,23,24) In our study hyperplasia was documented in 26% of all group with no endometrial carcinoma found, which matches the international results.…”
Section: Discussionsupporting
confidence: 90%
“…Adult variety is common accounts to 95%. [4] Generally the adult variety occurs in peri [40-45years] and post menopausal women with peak incidence at 50-55 years. The Juvenile one occurs in pre-pubertal age group.…”
Section: Discussionmentioning
confidence: 99%
“…Adult granulosa cell tumour (GCT) is a rare ovarian malignancy accounting for 1-2% of all tumours and 95% of germ cell tumours originating from sex cord-stromal cells. [1] .GCT can occur at any age but most commonly presents during the peri-menopausal or early postmenopausal period with median age of diagnosis between 50 and 54 years in most cases. [2] It is the most common hormoneproducing ovarian tumour which, usually produce oestrogen and leads to symptoms and signs of oestrogen excess.…”
Section: Introductionmentioning
confidence: 99%